Identifying the Factors of Online Game Acceptance Using Technology Acceptance Model - Findra Kartika Sari Dewi; Bunga Natalia (Indonesian Journal of Information Systems, 2021)
In the last two decades, many companies create online games. Online game is a game that is connected to the internet, where players can play and communicate with other players in different places at the same time. There are many types of game, such as adventure, strategy, cooking, make up, and so on. That is why a lot of people love to play online game. This study tries to identify the factors that support online game acceptance by students of Atma Jaya Yogyakarta University, because many students at this university play online games. The method used for this analysis is Technology Acceptance Model, which has main construct, namely Perceived ease-of-use (PEOU), Perceived usefulness (PU), Attitude toward use (ATU), Intention to use (ITU) and Actual Use (AU), and additional variables of Social Influence (SI), Personal (P) and Excitement (E) added by researcher. The data obtained to conduct this analysis using a questionnaire addressed to students. There are eleven hypotheses that serve as a reference in analyzing the relationship between variables. Each variable proves that each of these variables has a significant relationship in online game acceptance.